Urethral length measurement in women during sonographic urethrocystography – an analysis of repeatability and reproducibility - Wlaźlak, Edyta (J Ultrason, 2016)
There has been a rise in the use of sonographic urethrocystography in patients with a full bladder. So far, no publications have been made on the analysis of repeatability and reproducibility of the measurements performed during this procedure. AIM: An assessment of repeatability and reproducibility of urethral length measurements during sonographic urethrocystography in females with a full bladder in the introital approach, using real-time two-dimensional transvaginal ultrasound. MATERIAL AND METHODS: The ultrasound was performed in accordance with a standardized technique in female patients with a full bladder containing 200–300 mL of liquid. A total of 92 patients were included in the analysis. RESULTS: The Intraclass Correlation Coefficient for repeatability and reproducibility of urethral length measurements in sonographic urethrocystography ranged between 0.9217 and 0.9873 (p = 0.0000). The analysis of ultrasound urethral length measurements taken by two different physicians at an interval of several months confirmed their very high compatibility (ICC = 0.81, p = 0.000). CONCLUSIONS: Very good repeatability and reproducibility of urethral length findings during sonographic urethrocystography performed in accordance with the presented technique support the possible use of this type of examination in both clinical practice and research.